GAMBARAN INDEKS MASSA TUBUH (IMT) DAN KADAR KOLESTEROL TOTAL DALAM DARAH PADA PENGGUNA KONTRASEPSI HORMONAL JENIS MEDROXYPROGESTERONE ACETATE - MUHAMMAD IQBAL RIFAI FAUZI; ANDRI YUNAFRI (JURNAL ILMIAH SIMANTEK, 2020)
Contraception already popular, not only for family planning but also for prevent pregnancy. Oral contraception give sense ofsecurity for its user, because can be buy on store without anybody know. Injection Contraception and Implant usually have tofollow administrative procedure clinic and hospital. Oral or Injection, both have effect on increase body weight and obesity.On injection contraceptive user there is an increase blood pressure, BMI, total cholesterol, Low Density Lipoprotein (LDL),Triglycerides (TG), and Apoprotein B (Apo B). The goal of this study is to know description of BMI and total blood cholesterolon contraceptive hormonal user type medroxyprogesterone acetate. This is a descriptive study with cross – sectional designand point time approach. This study was conducted at Puskesmas Binjai Selatan Binjai city, This study held for 3 months onSeptember – December 2018. The result from this study is majority of contraceptive hormonal user typemedroxyprogesterone acetate with 6 months usage period have normal BMI and normal total blood cholesterol.Contraceptive hormonal user type medroxyprogesterone acetate, Majority of contraception user 20 – 35 age, number ofchildren ≥ 2, have job as housewife, majority of user have normal BMI and normal total blood cholesterol.